Assessment of willingness and determinants to receive the COVID-19 vaccine among the general population of the Somali region, Eastern Ethiopia: a 2021 cross-sectional study - Maereg Wolde; Yosef Wasihun; Trhas Tadesse; Addisalem Melesse; Rachana Sharma; Hnin Su Mon; Andinet Challa; Tesfaye Simireta; Hailemariam Addisu (BMJ Open)
Objective This research aimed to assess COVID-19 vaccine acceptance and the factors influencing it among the population of the Somali region in Ethiopia through a cross-sectional COVID-19 survey.Design Community-based cross-sectional study.Setting The survey was conducted in eight selected districts of the Somali region in Ethiopia from 20 October 2021 to 30 October 2021.Participants Participants were chosen using simple random sampling and data analysis used Stata V.14. Both bivariable and multivariable binary logistic regression methods were applied, with variables having a p value below 0.2 considered for inclusion in the final model, where statistically significant factors were identified at p<0.5.Primary outcome measure Willingness to take the vaccine.Results A total of 1010 respondents participated in this study. The proportion of people’s willingness to take the vaccine was 65% (95% CI 62 to 68). When you believe moderately or highly that getting a COVID-19 vaccine will protect others (AOR=6.2, 95% CI 1.43 to 26.6) and (AOR=7.2, 95% CI 1.7 to 29.7), then you will protect others as well. Whereas, a desire to get vaccinated little, moderately and highly (AOR=4.3, 95% CI 1.77 to 10.4), (AOR=20, 95% CI 8.5 to 47) and (AOR=147, 95% CI 55 to 392), respectively, was significantly associated with willingness to take the vaccine. Moreover having close family and friends who want them to get a COVID-19 vaccine (AOR=2, 95% CI 1.2 to 3.57) and religious leaders or community leaders (AOR=1.8, 95% CI 1 to 3.1) were significant factors in the multivariable logistic regression model.Conclusion This study found that COVID-19 vaccine acceptance was low in the Somali region. Factors positively linked to one’s willingness to get vaccinated included the belief that it protects others, personal desire for vaccination and support from family, friends, community and religious leaders.